Desempenho de forrageiras anuais de inverno sob distintos níveis de irradiância - Kirchner, Roque (2009)
This study aimed to determine possible effects in forage production and quality of the following annual winter forage: black oat (Avena strigosa Schreb) cv. Common, white oat (Avena sativa L.) cv. FAPA 2, ryegrass (Lolium multiflorum L,) cv. common, hairy vetch (Vicia villosa), wheat (Triticum aestivum L.) cv. dual purpose. BRS Tarumã under three different levels of irradiance (luminosity): a) full sunlight with 100% of irradiance b) level of 15x3 with 70% of irradiance and 222 trees per hectare and c) level of 9x3 with 21% of irradiance, with 370 trees/ha. The experimental design was completely randomized blocks, with split plots and three replicates. The ryegrass presented the highest production to all the irradiance levels, although the vetch presented the lower dry matter reduction under shading. There was higher water potential in plants and higher soil moisture under shading, however, forage production was strongly diminished (81%) at the lower irradiance levels. The crude protein increased while the total digestible nutrients decreased to most of the studied species in environment with lower levels of irradiance. The irradiance levels did not influenced the K content.